Control of plankton seasonal succession by adaptive grazing. (14th December 2012) - Mariani, Patrizio; Andersen, Ken H.; Visser, André W.; Barton, Andrew D.; Kiørboe, Thomas
Abstract : The ecological succession of phytoplankton communities in temperate seas is characterized by the dominance of nonmotile diatoms during spring and motile flagellates during summer, a pattern often linked to the seasonal variation in the physical environment and nutrient availability. We focus on the effects of adaptive zooplankton grazing behavior on the seasonal succession of temperate plankton communities in an idealized community model consisting of a zooplankton grazer and two phytoplankton species, one motile and the other nonmotile. The grazer can switch between ambush feeding on motile cells or feeding‐current feeding on nonmotile cells. The feeding‐current behavior imposes an additional mortality risk on the grazer, whereas ambush feeding benefits from small‐scale fluid turbulence. Grazer‐phytoplankton feeding interactions are forced by light and turbulence and the grazer adopts the feeding behavior that optimizes its fitness. The adaptive grazing model predicts essential features of the seasonal plankton succession reported from temperate seas, including the vertical distribution and seasonal variation in the relative abundance of motile and nonmotile phytoplankton and the seasonal variation in grazer abundance. Adaptive grazing behavior, in addition to nutrient and mixing regimes, can promote characteristic changes in the seasonal structure of phytoplankton community observed in nature.